ANALISIS POLA, FUNGSI, KALIMAT MINOR DALAM IKLAN PRODUK MINUMAN DI INSTAGRAM - Akromah, Dwi Fanan (Translation and Linguistics (Transling), 2023)
This research is based on the phenomenon of the emergence of minorsentences that occur in the barrel of advertisements on the social media platform Instagram.How is the form and function of words contained in minor sentences. The use of minorsentences is found in beverage products that are uploded on Instagram. To reveal the problemusing a syntactic approach, while still looking at the phenomenon that occurs in the minorsentences of beverage product ads on Instagram. This research uses qualitative methods. Theresearch data is a minor sentence contained in a drink ad on Instagram. There are threebeverage products collected including sprit_id, dancow, miloindonesia, and energen_id. Datawere collected in this study using the padan method and the agih method. Then the collecteddata will be paraphrased with the ujud change technique. From the data collected, there areseven minor sentence data in beverage product ads on Instagram. All collected data uses minorsentences in promoting product advertisements.